Ta'zir sebagai Pendidikan: Studi Living Hadith di Pondok Pesantren Al-Munawwir Komplek T Krapyak Yogyakarta - Abdul Hafizh Syaichu; Nurhadi; Ema Marhumah (Dialogia, 2026)
This research examines the practice of ta'zīr in Islamic boarding school Al-Munawwir dormitory area T Asy-Syathibi, Krapyak, Yogyakarta, positioning it beyond the binary debate of punitive coercion versus pedagogical idealism. While ta’zīr is frequently criticized in modern educational discourse as a behavioristic and violent disciplinary tool, this study addresses a critical gap by analyzing it as a pedagogical Living Hadith rather than a purely legalistic fiqh instrument. Employing a qualitative field methodology integrating Islamic Educational Philosophy (Ta’dīb) and Social Phenomenology. Data were gathered through prolonged participant observation, institutional document analysis, and in-depth interviews with administrators, active students, and alumni. The findings reveal that the theological foundation of ta’zīr relies on a functional reception of prophetic traditions balancing firmness and mercy. Consequently, its application shifts from physical coercion (dharb) to spiritual and academic restitution, such as mandatory Qur'anic recitation (nderes) and parental consultation (sowan), which are subjectively internalized by students as restorative tarbiyah. This study contributes to the reconceptualization of ta’zīr within global Islamic education by demonstrating how the integration of sacred texts generates a hybrid educational authority. Furthermore, it advances the conceptualization of Living Hadith as a dynamic social practice and outlines a comprehensive model for integrating maqasid-like ethics into institutional character-building frameworks.